Global wheat production could benefit from closing the genetic yield gap - Senapati, Nimai; Semenov, Mikhail A.; Halford, Nigel G.; Hawkesford, Malcolm John; Asseng, Senthold; Cooper, Mark; Ewert, Frank; Ittersum, Martin K. van; Martre, Pierre; Olesen, Jørgen E.; Reynolds, Matthew P.; Rötter, Reimund P.; et al. (Springer, 2022)
Global food security requires food production to be increased in the coming decades. The closure of any existing genetic yield gap (Yig) by genetic improvement could increase crop yield potential and global production. Here we estimated present global wheat Yig, covering all wheat-growing environments and major producers, by optimizing local wheat cultivars using the wheat model Sirius. The estimated mean global Yig was 51%, implying that global wheat production could benefit greatly from exploiting the untapped global Yig through the use of optimal cultivar designs, utilization of the vast variation available in wheat genetic resources, application of modern advanced breeding tools, and continuous improvements of crop and soil management.